PROFIL KOMPETENSI TERHADAP KESIAPAN KERJA MAHASISWA (STUDI KASUS MAHASISWA UNIVERSITAS GUNADARMA) - Astriya, Ugi; Mukhyi, Mohammad Abdul (Kompetensi (Competence : Journal of Management Studies), 2025)
This research focuses on analyzing the work abilities of management graduates at Gunadarma University. The analysis was conducted by measuring the role of academic achievement, internship experience, competence, and self-motivation. In addition, this study will also find out which factors most influence students' work readiness. This research uses a quantitative approach, with primary data obtained through an online questionnaire using Google Forms. A total of 250 respondents were selected through purposive sampling. Model testing was conducted on external and internal models. The research model was analyzed using SmartPLS4. This study reveals that academic achievement, internship experience, competence, and work motivation are the main factors that influence students' work readiness. Management students at Gunadarma University (Karawaci) scored quite high in all four factors. Of all the variables, work motivation was the most dominant factor influencing their work readiness.